Komparasi Perlindungan Hukum dalam Kontrak Pre-Project Selling Properti Indonesia dan Singapura - Putri Melati Nur Hidayah; Anjar Sri Ciptorukmi Nugraheni (Lembaga Pengembangan Kinerja Dosen, 2025)
This study compares the legal protection of pre-project selling property contracts in Indonesia and Singapore, focusing on the regulation of the position of PPJB, consumer protection, and the mechanism of transfer of ownership and payment. The approach used is normative with legislative and comparative methods, relying on primary and secondary legal materials through literature studies. Descriptive and comparative analysis reveal significant differences in the legal arrangements of the two countries. In Indonesia, Law No. 8 of 1999 and Law No. 1 of 2011 regulate pre-project selling through PPJB, but supervision is weak so that it often harms consumers, such as in the case of Meikarta. In contrast, Singapore has more detailed regulations, such as the Housing Developers (Control and Licensing) Act, which requires escrow accounts for consumer funds and strict payment schemes. Supervision and law enforcement in Singapore are more effective with strict sanctions against violations, reinforced by jurisprudence such as the Jurisprudence of Tan Eck Hong v Maxz Universal Development Group Pte Limited (2012) SGHC 240. This study concludes that legal protection in Singapore is more advanced than Indonesia, providing important recommendations for property law reform in Indonesia to prevent disputes and abuse in property transactions.